P182 Awareness of sleep hygiene amongst healthcare practitioners (HCP). (12th November 2019) - Devani, N; Shah, A; Mandal, S
Abstract : Background: Sleep problems are estimated to affect up to 1/3 of the population, 1 contribute to reduced physical and mental health and sleep-related productivity losses in the UK are estimated at £30bn/p.a. 1 Limited studies within this area suggest that for many patients, sleep problems are often minimised or misattributed by HCPs. 2 A lack of awareness and adherence to sleep hygiene practices is a recognised contributor to sleep problems. We wished to understand the awareness of these practices amongst hospital HCPs delivering patient care since admissions provide an ideal opportunity to discuss good sleep hygiene with patients. Method: HCPs at a London teaching hospital were invited to complete a survey assessing their understanding of 18 sleep hygiene practices and rate their own adherence to these practices and overall sleep quality. Results: 116 HCPs participated: 92% doctors, 8% registered nurses. Only 57% had inquired about patient sleep quality during routine clinical interactions and most (90%) only ask when relevant to the presenting complaint. HCP self-reported awareness of sleep disorders using a Likert scale (1 to 10; 1=limited understanding; 10=extensive knowledge) revealed a score of 4.9±2.03. Assessment of their own sleep quality demonstrated a score of 6.01±2.3 (Likert scale of 1–10; 1=poor quality with frequent waking and difficulty initiating sleep; 10=excellent quality regular, refreshing sleep). Perceptions of selected sleep hygiene practices and an evaluation of their own practices have been summarised in figure 1. Conclusion: Despite the prevalence of sleep problems, most HCPs do not routinely inquire into a patient's sleep quality. Furthermore, there is a variable level of awareness of sleep hygiene practices and many HCPs themselves undertake practices which may impact negatively on sleep. In order to advise patients appropriately, HCPs will require a better understanding of such practices thus highlighting the need for further training in this important area. References: Hafner M, et al . The economic costs of insufficient sleep: a cross-country comparative analysis. Rand Health 2017;Q; 6:11. Vyas J, et al . Patients' and clinicians' experiences of consultations in primary care for sleep problems and insomnia. British Journal of General Practice 2010;60(574):e180–e200.